2021
DOI: 10.1007/978-3-030-78098-2_12
|View full text |Cite
|
Sign up to set email alerts
|

Using a Low Code Development Environment to Teach the Agile Methodology

Abstract: The Agile development methodology is soaring in popularity in the business world. Companies are turning to Agile to develop products quickly and to achieve digital transformation of their organization. Because of this push, companies need employees who understand Agile. Therefore, higher education is obligated to provide an understanding of Agile to students as they enter the workplace. Providing Agile experience to students who are new to programming is difficult because they are so worried about the coding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…One remedial measure is to use low code or no code development platforms. As a result, students spend less time learning to create applications and can experience and understand agile rituals and roles [14].…”
Section: Development Trendsmentioning
confidence: 99%
“…One remedial measure is to use low code or no code development platforms. As a result, students spend less time learning to create applications and can experience and understand agile rituals and roles [14].…”
Section: Development Trendsmentioning
confidence: 99%
“…A case study of integrating Agile into student capstone projects found that while teaching Agile practices is challenging, it is worthwhile because it enriches students’ software development experience (Lu and DeClue, 2013). Three studies on integrating the Agile practice of prototyping, using low-code tools and robotic process automation, show students feel the Agile skills they gained are valuable for the job market (Lebens, 2021; Lebens et al , 2023; Lebens and Finnegan, 2021). The authors of one study on integrating agile into the classroom concluded that agile practices “should be used in any college course requiring collaboration, group projects, or problem solving,” based on how practices such as stand-up meetings foster communication between students (May, 2016).…”
Section: Integrating Stand-up Meetings Into the Classroommentioning
confidence: 99%
“…An example of how those competencies could be achieved is the experience of working in an agile team. Therefore, no-code platforms in combination with agile methods and agile practices are used (Lebens and Finnegan, 2021). AI assistants can support students who are not primarily studying computer science to gain this experience.…”
Section: Humansmentioning
confidence: 99%